(untitled) (Research, Society and Development, 2025)
The findings highlight the importance of screening and diagnosis, emphasizing the consolidation of the Edinburgh Postnatal Depression Scale (EPDS) as the main tool for identifying depressive symptoms during the puerperal period, recognized for its sensitivity in detecting women who may be at risk for postpartum depression Nursing plays a essencial role during the puerperal period, providing assistance in both physical and mental care. Regarding mental health, considering postpartum depression as a highly relevant issue today, nurses can act in counseling, support, and meeting basic human needs. This study aims to investigate the impact of postpartum depression on women, infants, partners, and families, as well as how nursing can intervene in this process.